Report of Strategic Studies in China (2019) Once-in-a-Century Transformation and China’s Period of Strategic Opportunity - Men, Honghua; Xiao, Xi (Springer Nature Singapore : Imprint: Springer, 2021)
XXII, 167 p. 3 illus., 1 illus. in color.